2016
DOI: 10.1111/appy.12265
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine for schizophrenia: A survey of randomized trials

Abstract: Most treatment approaches-and some in common use-have only one or two relevant small trials. Some coordination of effort would help ensure that further well-designed appropriately sized randomized trials are conducted. Systematic reviews should be performed in this field but with titles that take into account the complexity of TCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Among the most commonly evaluated treatments are Ginkgo biloba, acupuncture, Wendan decoction and Shugan Jieyu capsule. As the TCM is a very broad concept, the article suggested more specific intervention terms should be adopted (Deng, et al, 2016).…”
Section: Article Title Objective Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the most commonly evaluated treatments are Ginkgo biloba, acupuncture, Wendan decoction and Shugan Jieyu capsule. As the TCM is a very broad concept, the article suggested more specific intervention terms should be adopted (Deng, et al, 2016).…”
Section: Article Title Objective Resultsmentioning
confidence: 99%
“…The results showed Traditional Chinese Medicine (TCM) presents several pharmacological interventions, not only acupuncture, but other measures based on the search for patients' well-being (Deng & Adam, 2016). Therefore, this term TCM is quite broad, since there were a large number of measures evaluated, demonstrating the researchers' interest in this practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant sudies show that TCM such as Ginkgo biloba L . and Wendan decoction ( Singh et al, 2010 ; Deng and Adams, 2016 ) has beneficial effects on patients with schizophrenia. Thus, we found that TCM such as Ginkgo biloba L. extract (EGb), which enhanced the effectiveness of the antipsychotic drug haloperidol and reduced its extrapyramidal side effects ( Zhang et al, 2001a ), can also be used as an add-on therapy for chronic schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Chinese herbal medicine has been used to treat millions of people with schizophrenia for thousands of years. It may improve some prognosis of schizophrenia ( Rathbone et al, 2007 ), and there is little evidence of side effects ( Deng and Adams, 2016 ). Chinese herbal medicine can be used alone or in combination with other stimulants according to the patient's condition.…”
Section: Introductionmentioning
confidence: 99%